The Influence of Gross Domestic Product and Remittances on Indonesia's Economic Growth, 2010–2024 - Aldi Bagus Prakoso; Vira Amilia Fikrotun Nabila; Alya Rachma Silviana; Qismah Nuroniyyah Hidayati; Muhammad Yusuf Aria Widjaja (Lensa Ilmiah: Jurnal Manajemen dan Sumberdaya, 2026)
Economic growth is one of the primary indicators used to assess a country's economic performance and development success. In Indonesia, economic growth is influenced by various macroeconomic factors, including Gross Domestic Product (GDP) and remittances from migrant workers. This study aims to examine the effects of GDP and remittances on Indonesia’s economic growth during the period 2010–2024. The study employs a quantitative explanatory approach using secondary data obtained from Statistics Indonesia (BPS) and Bank Indonesia (BI). The data were analyzed using multiple linear regression with the assistance of SPSS version 25. Prior to regression analysis, classical assumption tests, including normality, heteroscedasticity, multicollinearity, and autocorrelation tests, were conducted to ensure the validity of the model. The results indicate that GDP has a statistically significant relationship with economic growth (p = 0.021), whereas remittances do not have a significant effect (p = 0.221). Simultaneously, GDP and remittances significantly influence economic growth, as indicated by an F-statistic significance value of 0.042. The coefficient of determination (R²) shows that the independent variables explain 41.1% of the variation in economic growth, while the remaining 58.9% is explained by other factors outside the model. Although GDP was found to have a negative coefficient, this result should be interpreted cautiously due to the conceptual proximity between GDP and economic growth as well as the characteristics of the data used. The findings suggest that strengthening domestic productive capacity remains essential for sustaining economic growth, while efforts are needed to encourage the productive utilization of remittances to enhance their contribution to national economic development.